Aportes de responsabilidad social corporativa de la sociedad portuaria de Santa Marta - SPMS. análisis desde una perspectiva socio – ambiental. (2020)
Corporate social responsibility seeks a balance between the social, economic and environmental to contribute to the objectives of the company and the community. The purpose of this work is to highlight the environmental contributions made by companies that affect in one way or another the conservation of the environment, seeking to generate a commitment to preservation, development and protection of the environment.